2015
DOI: 10.1007/s12223-015-0411-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of zinc chloride precipitation method for rapid isolation and concentration of infectious Pectobacterium spp. and Dickeya spp. lytic bacteriophages from surface water and plant and soil extracts

Abstract: This is the first report describing precipitation of bacteriophage particles with zinc chloride as a method of choice to isolate infectious lytic bacteriophages against Pectobacterium spp. and Dickeya spp. from environmental samples. The isolated bacteriophages are ready to use to study various (ecological) aspects of bacteria-bacteriophage interactions. The method comprises the well-known precipitation of phages from aqueous extracts of the test material by addition of ZnCl2, resuscitation of bacteriophage pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…For example, virus titers, including phage titers in sea water can be relatively low necessitating preparatory concentration of the sample [41] that is typically done by filtration, precipitation, or a combination of both [3,42]. Czajkowski and colleagues [43], for example, demonstrated that zinc chloride could be used to concentrate phages from water or plant or soil extracts sufficiently to detect phages by direct plating without enrichment culture. They suggested that this gave a more accurate sampling of the diversity of phages in their samples.…”
Section: Phage Isolation Methodsmentioning
confidence: 99%
“…For example, virus titers, including phage titers in sea water can be relatively low necessitating preparatory concentration of the sample [41] that is typically done by filtration, precipitation, or a combination of both [3,42]. Czajkowski and colleagues [43], for example, demonstrated that zinc chloride could be used to concentrate phages from water or plant or soil extracts sufficiently to detect phages by direct plating without enrichment culture. They suggested that this gave a more accurate sampling of the diversity of phages in their samples.…”
Section: Phage Isolation Methodsmentioning
confidence: 99%
“…This approach is better suited to non-faecal samples and is routinely used to study aquatic environments. Similarly, zinc chloride and ammonium acetate precipitation protocols to concentrate phages are more suited to non-faecal samples [ 42 , 43 ].…”
Section: Vlp Isolationmentioning
confidence: 99%
“…The supernatants were sterilized treated with 5% v/v chloroform which safely inactivates any bacteria as well as enveloped viruses but will generally leave most Caudovirales intact [16]. Subsequently, viral particles were precipitated by adding 1 ml of a 2 M ZnCl 2 solution per 50 ml of sample, mixing shortly by inversion, and incubating the suspension at 37°C without agitation for 15 minutes [129]. After precipitation, the samples were centrifuged again at 8'000 g for 15 minutes and the supernatant was discarded.…”
Section: Bacteriophage Isolation Basic Proceduresmentioning
confidence: 99%